Prevalence and causes of blindness and severe visual impairment (BL/SVI) among children in Ntungamo district, Southwestern Uganda: A key informant cross-sectional population survey - Arunga, S.; Onyango, J.; Ruvuma, S.; Twinamasiko, A. (The Journal of Ophthalmology of Eastern, Central and Southern Africa, 2016)
To estimate the prevalence and causes of blindness and severe visual impairment among children in Ntungamo district South-western, Uganda.Methods: This was a cross sectional community survey using the key informant method; approximately 200 village health team members were carefully selected and trained to screen for severe visual impairment using a torch, 6 meter string and a 6/60 E chart. They did house to house screening for severe visual impairment and blindness among children below 16 years in the whole district. Identified children were referred to a rendezvous point within the community to be examined further by the ophthalmologist. Data was collected using the standardized WHO childhood blindness data collection form. Proportions and causes of severe visual impairment and blindness were determined. Clinical and social characteristics were described.Results: A total of 59 children were identified, 15 with severe visual impairment and 44 with blindness. Mean age was 6.5 years (95% CI 5.3-7.4) and 59% of the children were male. The prevalence of blindness and severe visual impairment was 0.02% (95% CI 0.01-0.03). Causes were analysed by anatomical site, aetiology and specific diagnosis. Majority of the anatomical causes were due to cornea (18%) and lens (17%) abnormalities. With respect to specific diagnosis, 30% was cataract and cataract surgery complications and corneal scar. Overall, 72% of the blindness and severe visual impairment was due to avoidable causes.Conclusion: Prevalence of severe visual impairment and blindness was relatively low in this population. Lens and corneal abnormalities were the leading cause of blindness. Most of the cases of visual impairment and blindness were avoidable.
Keywords: Blindness; Visual impairment (BL/SVI); Children